Isolation of Human Monoclonal scfv Antibody Specifically Recognizing the D2-5-Ht1a Heteromer. - Łukasiewicz, Sylwia; Fic, Ewelina; Bzowska, Monika; Dziedzicka-Wasylewska, Marta (Journal of New Developments in Chemistry, 2019)
Antibody phage display has become a useful technique for discovering and optimizing target-specific monoclonal antibodies suitable for many applications, including therapeutic ligands, which may act as direct pharmacological compounds or may be used as targeting ligands for controlled drug delivery. Recently, the D2-5-HT1A heteromer, which is formed by the dopamine D2 and serotonin 5-HT1A receptors has attracted attention as a potential target of antipsychotic drugs. Therefore, the aim of the study was to identify scFv monoclonal antibodies that are able to specifically recognize epitopes formed within the heteromer structure. Because both receptors are membrane proteins, it is important to conduct bio-panning experiments in the most natural conditions, in which the presented antigens (D2-5-HT1A heteromers) are in their native form and possibly in their best-preserved spatial structure. It has been shown here that phage display methodology can be successfully used in the preparation of monoclonal antibodies against dimers of membrane proteins. To separate phages specifically binding the D2-5-HT1A heteromer, the selection process using CHO+ cells with overexpression of both receptors was conducted. Phages that were bound to receptor monomers or other CHO-K1 cell surface proteins were eliminated as a result of negative selection by using CHO- cells expressing separate receptor monomers.
Keywords: phage display; scFv antibody; D2-5-HT1A hetromer; nanotechnology